Profitabilitas dan Risiko Bank: Perspektif Mediasi Capital Adequacy Ratio pada Industri Perbankan Indonesia - Eka Sulistiyana; Gunarianto; Survial (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This study aims to analyze the effect of funding decisions on bank profitability, with the Capital Adequacy Ratio (CAR) as a moderating variable. The object of the study is conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The independent variables analyzed include company size (SIZE), non-performing loans (NPL), operational efficiency (BOPO), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM), with Return on Assets (ROA) as the dependent variable. The research method uses a quantitative associative-causal approach, with multiple linear regression analysis techniques and Moderated Regression Analysis (MRA). The results of the study indicate that simultaneously, the variables SIZE, NPL, BOPO, LDR, and NIM have a significant effect on ROA. Partially, NPL and BOPO have a significant negative effect on ROA, while NIM has a significant positive effect. SIZE and LDR have no significant effect on ROA. The CAR variable was shown to moderate the effects of SIZE, BOPO, and NIM on ROA, but was ineffective in significantly moderating the effects of LDR and NPL. This finding underscores the importance of managing funding structure and capital adequacy in improving banking profitability. This research contributes to policymakers and bank management in formulating financial strategies oriented towards efficiency and business sustainability